Rapid and Efficient Purification of Functional Collectin-12 and Its Opsonic Activity against Fungal Pathogens. (29th July 2019) - Zhang, Jie; Li, Anna; Yang, Chang-qing; Garred, Peter; Ma, Ying Jie
Abstract : Collectin-12 (collectin placenta 1, CL-P1, or CL-12) is a newly identified pattern recognition molecule of the innate immune system. Recent evidences show that CL-12 plays important roles not only in innate immune protection against certain clinically important pathogens but also in scavenging of host molecules, leukocyte recruitment, and cancer metastasis. Furthermore, CL-12 has been shown to be associated with the pathogenesis of human diseases such as Alzheimer's disease and multiple sclerosis lesion development. Therefore, the functional consequence of CL-12 remains intriguing and awaits further elucidation. However, available protocols for the purification of recombinant CL-12 with high purity are laborious and inefficient and hamper further functional studies. Here, we report a simple, rapid, and efficient solution to obtain biologically active CL-12 with high purity. We established stable transfected Flp-In™-CHO cells expressing the recombinant CL-12 extracellular domain in high amounts. Recombinant CL-12 was purified from cell culture supernatants using a 3-step rapid purification procedure utilizing disposable affinity and ion exchange minicolumns. Purified recombinant CL-12 adopted an oligomeric structure with monomers, dimers, and trimers and retained its binding capacity towards the A. fumigatus strain that has been described before. Furthermore, we demonstrated the opsonic properties towards eight clinical isolates of A. fumigatus strains and diverse clinically important fungal pathogens. Purified recombinant CL-12 revealed a differential binding capacity towards selected fungal pathogens in vitro. In conclusion, we demonstrate a rapid and efficient purification solution for further biochemical and functional characterization of CL-12 and reveal opsonic properties of CL-12 towards diverse fungal pathogens.